Improving food security and safety through use of edible by-products from wild game - McCrindle, C.M.E.; Siegmund-Schultze, M.; Heeb, A.W.; Zárate, Anne Valle; Ramrajh, S. (Springer, 2013)
Game harvesting in South Africa generally leaves behind edible by-products, which could be a low-cost source of protein for poor people in rural areas. Seven professional and nine recreational hunters were interviewed, a game harvest and trophy hunt attended and literature reviewed, in order to describe the food value chain for game and ways in which edible by-products could be legally channelled into the human food chain, rather than being left in the field for scavengers. Practices of informal vendors (n = 51) were assessed using structured interviews, observation and microbiological analysis. In an experiment, inspected game by-products (shinbones from impala and springbok) were provided to eight informal traders for cooking at an informal market and microbiological analysis was done before and after preparation. The results showed that providing edible by-products to poor consumers appears to be culturally acceptable, affordable, accessible and safe. A crossover from formal to informal marketing is recommended as it would enhance traceability and safety of the product and minimise the risk of poaching. It is suggested that methods should be developed which make the distribution of edible by-products to vulnerable rural communities feasible.